Responsible tourism in Cyprus: The rhetoric and the reality - Farmaki, Anna; Constanti, Panayiotis; Yiasemi, Irene; Karis, Phidias (My University, 2014)
Purpose: This paper aims to provide an overview of the approaches that industry stakeholders follow towards responsible tourism in Cyprus and to address the challenges that responsible tourism management faces in a mass tourism destination. Design/methodology/approach: In doing so, the paper discusses the concept of responsible tourism and its application in the hospitality and tourism industry. A qualitative research approach was followed whereby roundtable discussions between industry leaders and hospitality educators were initiated in order to identify key challenges. In addition, secondary research was performed with relevant data presented in the paper being previously collected by the CSTI (Cyprus Sustainable Tourism Initiative). Findings: Findings reveal that responsible tourism adoption in Cyprus is minimal. Several challenges have been identified as barriers to adoption and successful implementation including poor understanding of the concept, lack of awareness, limited budget, lack of coordination of activities and the absence of an integrated system to ensure cooperation and of a monitoring mechanism. Practical implications: The paper will be of immense value to industry practitioners as it represents a holistic understanding of the challenges facing hospitality and tourism industry stakeholders in terms of the implementation of responsible tourism practice. Propositions are made regarding the maximisation of the benefits of responsible tourism. Originality/value: The paper draws on sustainability issues in an attempt to shed light on the role of responsible tourism in the hospitality and tourism industry in Cyprus and consequently advances knowledge on responsible tourism management offering value to academics practitioners and students alike.
Keywords: Cyprus; Hospitality; Responsible tourism; Sustainability; Tourism